2018
DOI: 10.48550/arxiv.1810.04553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Complexity of Solution Extension of Optimization Problems

Abstract: The question if a given partial solution to a problem can be extended reasonably occurs in many algorithmic approaches for optimization problems. For instance, when enumerating minimal dominating sets of a graph G = (V, E), one usually arrives at the problem to decide for a vertex set U ⊆ V , if there exists a minimal dominating set S with U ⊆ S. We propose a general, partial-order based formulation of such extension problems and study a number of specific problems which can be expressed in this framework. Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Proof. For k = 3, the result follows from [5] and the previous discussion. Now, let us prove it for k = 4.…”
Section: P K -Free Graphsmentioning
confidence: 52%
See 1 more Smart Citation
“…Proof. For k = 3, the result follows from [5] and the previous discussion. Now, let us prove it for k = 4.…”
Section: P K -Free Graphsmentioning
confidence: 52%
“…It is proven in [5], among other results, that the extension problem with A = ∅ is NP-complete in the case of maximal matchings. Since maximal P 3 -free graphs are exactly maximal matchings in triangle-free graphs, this result implies that the edge extension problem for P 3 -free graphs is NP-complete, even in triangle-free graphs and with A = ∅.…”
Section: P K -Free Graphsmentioning
confidence: 99%
“…Since this result was first announced, Bläsius et al [6] have also proven the extension problem for minimal hitting sets to be W[3]-complete using different techniques. The latter has subsequently been improved by Casel et al [11], they have shown that already the special case of extension to minimal dominating sets in bipartite graphs is hard for W [3]. Finally, building on the work presented here, Hannula, Song, and Link [32] have very recently identified independence detection in relational databases as another representative of this class.…”
Section: Introductionmentioning
confidence: 57%